Reperfusion strategy in Europe: temporal trends in performance measures for reperfusion therapy in ST-elevation myocardial infarction - Schiele, François; Hochadel, Matthias; Tubaro, Marco; Meneveau, Nicolas; Wojakowski, Wojtek; Gierlotka, Marek; Polonski, Lech; Bassand, Jean-Pierre; Fox, Keith A.A.; Gitt, Anselm Kai (European heart journal, 2010)
The rate and type of reperfusion, as well as time delays to reperfusion are directly associated with mortality and are established as performance measures (PMs) in the treatment of ST elevation myocardial infarction (STEMI). To date, little information exists about PMs for reperfusion in clinical practice in Europe and their temporal changes.Using the Euro Heart Survey ACS-III data set (2 years of inclusions between 2006 and 2008, 138 centres in 21 countries), we selected patients with STEMI eligible for reperfusion therapy. Recorded variables corresponded to the CARDS data set. The rate and type of reperfusion, as well as door to needle and door to artery times were assessed and compared between periods. Timely reperfusion was defined as a door to needle time <30 min, or a door to artery time <90 min. We assessed changes in PMs for reperfusion over the 2 years of recruitment. Among 19 205 patients included in the registry, 7655 had STEMI, and 6481 were admitted within the first 12 h and eligible for reperfusion. The rate of patients who underwent reperfusion increased from 77.2 to 81.3%, with an increase in the use of primary percutaneous coronary intervention (P-PCI). The door to needle and door to artery times decreased significantly during the study period, from 20 to 15 min (P = 0.0011) and from 60 to 45 min (P < 0.0001) respectively. As a result, the number of eligible patients receiving reperfusion therapy in a timely manner increased from 53.1 to 63.5% (P < 0.0001). In parallel, over the 2-year period, in-hospital mortality decreased from 8.1 to 6.6% (P = 0.047).In centres participating in the Euro Heart Survey ACS III, PMs for reperfusion in STEMI improved significantly between 2006 and 2008, with greater use of PCI. Similarly, the rate of patients reperfused in a timely manner also increased, with a significant reduction in door to needle and door to artery times.
Gesehen am 28.06.2023